Faktor-faktor yang Memengaruhi Alih Fungsi Lahan Pertanian di Kabupaten Serang Menggunakan Geographically Weighthed Regression (GWR) - Hasanah, Faujatul; Jafaruddin, Nurhana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Land is an important natural resource in production, but its availability is limited amidst increasing demand due to population growth and economic activity. Serang Regency, with its strategic geographical position, is experiencing conversion of agricultural land to housing, industry, and infrastructure sectors, causing a decrease in the area of paddy fields from 48,925 hectares in 2015 to around 46,000 hectares in 2023. This study analyzes the factors that influence the conversion of agricultural land in Serang Regency using the Geographically Weighted Regression (GWR) method, focusing on the variables of population growth, number of industries, and agricultural productivity. The results showed that the largest land conversion occurred in Pabuaran, Baros, Mancak, Ciruas, and Tanara sub-districts. The results of GWR modeling of the relationship between population and agricultural land conversion show a positive value, indicating that the increase in agricultural land conversion is not only influenced by population. The number of industries shows a negative coefficient value, with the highest influence occurring in sub-districts in the eastern region of Serang Regency. Land productivity has a positive and significant effect on agricultural land conversion in all sub-districts. Therefore, policies that support increased agricultural productivity are needed to reduce the rate of agricultural land conversion.